THE EFFECTIVENESS OF CRIMINAL SANCTIONS FOR DRUGS USERS IN REALIZING REHABILITATION GOALS - Fatimah Zahro Rizqiyah; Selamat Lumban Gaol; Sudarto (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
Drug abuse is a serious problem with broad impacts on health, social aspects, and the criminal justice system in Indonesia. Law Number 35 of 2009 concerning Narcotics regu-lates criminal sanctions for drug users by placing medical and social rehabilitation as an important part of the drug abuse prevention policy. However, in law enforcement practice, the application of criminal sanctions against drug users is still dominated by im-prisonment, thus raising questions about its effectiveness in achieving rehabilitation goals. This study aims to analyze the effectiveness of the application of criminal sanctions against drug users in achieving rehabilitation goals under the Indonesian criminal law system, and to identify factors that influence its effectiveness. The research method used is normative legal research with a statutory, conceptual, and case approach. The analysis was conducted qualitatively through a review of laws and regulations, legal doctrine, and court decisions related to the punishment and rehabilitation of drug users. The results of the study indicate that the application of criminal sanctions against drug users is not fully effective in achieving rehabilitation goals. This is influenced by the persistently repressive paradigm of criminal justice, limited rehabilitation facilities and infrastructure, and suboptimal official understanding and coordination among law enforcement. Furthermore, legal culture and public perception of drug users also influence the direction of criminal punishment. Therefore, strengthening rehabilitative-oriented criminal justice policies, integrating the criminal justice system, and shifting the law enforcement paradigm are necessary so that criminal sanctions truly function as an instrument of recovery and community protection.